FAKTOR-FAKTOR STRES PADA IBU RUMAH TANGGA DALAM MENGHADAPI KEGIATAN BELAJAR DARI RUMAH (BDR) - Windayani; Pratiwi Sakti (JURNAL PSIMAWA, 2020)
This study aims to determine the factors cause stress to housewives in dealing with Learning from Home (BDR). This research method uses a qualitative descriptive method. Data collection technique uses interview, observation, and documentation techniques. Data analysis techniques, namely; data collection, data reduction, data presentation and conclusions. Then in using data validity techniques; including using triangulation source, triangulation method, and triangulation theory. In this study, the researcher uses three subjects whom are housewives aged 29-36 years and have children who are in PAUD, TK or SD. The result of the study indicates that there are symptoms of stress in housewives caused by stress factors during BDR (learning from home) activities such as irritability and decreased concentration.